2017
DOI: 10.1007/s10792-017-0554-y
|View full text |Cite
|
Sign up to set email alerts
|

Crossover clinical trial of pain relief in cataract surgery

Abstract: PurposeTo determine the effects of intra-operative Korean traditional music on pain experienced by Korean patients undergoing sequential bilateral cataract surgery.MethodsThis was a two-sequence, two-period, and two-treatment crossover study. Fifty-two patients with cataracts were divided into two groups by block randomization, and bilateral cataract surgery was performed. In group 1, patients listened to Korean traditional music (KTM) during their first but not second cataract surgery. This sequence was rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Prior studies have observed significant differences in pain relief between music and non-music conditions [ 11 , 37 , 38 ]. Differences have also been observed between music and other auditory conditions (i.e., white noise) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have observed significant differences in pain relief between music and non-music conditions [ 11 , 37 , 38 ]. Differences have also been observed between music and other auditory conditions (i.e., white noise) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Music has been investigated as a potentially viable non-pharmacological treatment for alleviating pain [ 7 9 ]. Additionally, listening to music along with taking oral sedatives during cataract surgery reduced anxiety and enhanced comfort [ 10 ], diminishing the experience of pain during the surgery [ 11 ]. Recent research has revealed that music plays a critical role in dispersing harmful stimulants in order to transform cognitive faculties and emotions as an “audio analgesic” [ 9 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 121 randomly selected elderly patients [ 4 ] found that relaxing music during surgery led to a more satisfying experience. While several studies have shown similar results for cataract surgery [ 5 – 7 ], the benefits of music for intravitreal injection have not been well studied. Currently, there is only one randomized clinical trial conducted by Chen which suggested music could play a significant role in reducing anxiety during intravitreal injections, as reflected from the decrease in the anxiety level as measured by the state anxiety portion of the Spielberger State-Trait Anxiety Inventory (STAI-S) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of music have been used in previous studies of their effect on patient experience in cataract surgery, including “classical music accompanied by soothing sounds of nature”, meditation music, and Korean traditional instrumental music [ 4 , 6 , 7 ]. The Korean study highlighted a possible cultural factor on the type of music in different populations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%